Effectiveness of school-based brief cognitive behavioral therapy with mindfulness in improving the mental health of adolescents in a Japanese school setting: A preliminary study - Kato, Kiun; Matsumoto, Yuki; Hirano, Yoshiyuki (Frontiers in Psychology, 2022)
Background: Emotional regulation is important for adolescents’ adaptive development. Preventive interventions for anxiety and depression are necessary for reducing the development of disorders later in life, and emotional regulation is a potentially relevant factor. Objective: We investigated the effects of a mindfulness-based psychological education and prevention program (Mindfulness and Awareness Program, MAP) on the mental health of junior high school students in Japan. Methods: Our MAP primarily focused on mindfulness meditation to improve emotional regulation and, thereby, reduce depression and anxiety. MAP comprised eight sessions (20 min each) administered by a school counselor in a school setting. All participants (N = 349) were 12–13-year-old adolescents from nine classes in two Japanese schools. The program was provided to the intervention group, wherein students were educated on emotional expression, emotional cognition, and emotional regulation. The control group received regular school counseling services. Results: Compared to the control group, the intervention group showed significant improvement in emotional regulation and a decrease in depression and generalized anxiety. The effect was greater at follow-up assessment than immediately post intervention, and in female than male students. Conclusions: Our mental health prevention program could be applicable to junior high school students in Japanese school settings.